Pengaruh Art Therapy Terhadap Peningkatan Harga Diri dan Kualitas Hidup pada Pasien dengan Berduka di Desa Bunut Wetan - Hasanah, Fitriatul; Widowati, Sri (Pustaka Galeri Mandiri, 2026)
Grief is a natural response to the loss of a loved one. However, prolonged grief may negatively affect an individual's psychological well-being, leading to decreased self-esteem and poor quality of life. Art therapy is a non-pharmacological intervention that can help individuals express emotions, improve self-acceptance, and enhance psychological well-being.Objective: To determine the effect of art therapy on improving self-esteem and quality of life in a patient experiencing grief. This study employed a descriptive case study design using the nursing process approach, including assessment, diagnosis, intervention, implementation, and evaluation. The subject was a 60-year-old woman experiencing grief following the loss of her husband. Art therapy was administered in eight sessions over four weeks, with a frequency of two sessions per week. Self-esteem was measured using the Rosenberg Self-Esteem Scale (RSES), while quality of life was assessed using the World Health Organization Quality of Life-BREF (WHOQOL-BREF) questionnaire before and after the intervention. The intervention resulted in an improvement in self-esteem, with the RSES score increasing from 14 (low self-esteem) to 17 (normal self-esteem). Quality of life also improved, with the WHOQOL-BREF score increasing from 46.25 (poor quality of life) to 50 (good quality of life). Throughout the intervention period, the patient demonstrated better emotional expression, increased social interaction, improved self-acceptance, and a more positive outlook on life. Art therapy appears to be effective in improving self-esteem and quality of life among grieving patients. This intervention can serve as a beneficial complementary nursing therapy to facilitate emotional expression, enhance self-acceptance, and support psychological adaptation during the grieving process.